The Implementation of Flash Card to Improve Simple English Vocabulary for Young Learners - Diva Firliana Deswita; Husni Mubarok (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research explores the effectiveness of flashcards as a tool for enhancing vocabulary mastery among young English learners. The study was conducted at SD Negeri 6 Ngabul Jepara with a sample of 40 fourth-grade students, utilizing a pre- experimental design that included pre-tests and post-tests. Flashcards were employed over multiple instructional sessions to teach vocabulary related to body parts, locations, and animals. The results, analyzed through paired sample t-tests, revealed a significant enhancement in students' vocabulary skills, with the post-test mean score (58.87) considerably exceeding the pre-test mean (50.79), and a p-value of 0.002 indicating statistical significance. The study concludes that flashcards effectively improve students' vocabulary retention and motivation, making the learning process more engaging and successful. These findings suggest that flashcards serve as a valuable instructional tool for language learning, especially at the elementary level.